Assessment of Open Defecation Practice Among Almajiri Schools in Kware Local Government, Sokoto State, Nigeria: Preventive Lessons from Sokoto Caliphate Ideals - Bashar, Tambari Abbas (Darul Yasin Al Sys, 2025)
Almajiri schools in Nigeria face challenges, including poor sanitation and open defecation. This study assessed the situation of Almajiri schools in Kware Local Government, Sokoto State, Nigeria, regarding open defecation and proffered comparative preventive solutions from Sokoto Caliphate ideals. A semi-structured questionnaire was administered to 50 Almajiri schools, and data were analyzed using descriptive statistics. And a historical comparative method was used to link the result with the qualitative information from Sokoto Caliphate literatures or information. The results showed: 1. Poor sanitation: 50% of schools had open defecation, and 20% had scarce toilets. 2. Water scarcity: 50% of schools had no source of water supply. 3. Poor environmental sanitation: 50% of schools had bad environmental sanitation. 4. Hazardous waste management: 46% of schools practiced open dumping, and 28% practiced open burning. The study highlights the need for improved sanitation, water supply, and waste management in Almajiri schools. The Sokoto Caliphate ideals, which emphasize Zakat, seeking for wealth to earn livelihood, cleanliness and hygiene, can provide valuable lessons for preventing open defecation and promoting better sanitation practices.